Effectiveness of Group Counseling with Self-Control Techniques to Reduce Anger in Adolescents - Susilo, Dwi Amalia; Lubis, Saiful Akhyar (Yayasan Sembilan Pemuda Indonesia, 2025)
This quasi-experimental study evaluated the effectiveness of group counseling with self-control techniques in reducing anger among 19 eighth-grade students at UPT SMPN 22 Medan, Indonesia. The research employed a pretest-posttest control group design, with anger levels assessed using the Clinical Anger Scale (Snell et al., 1995). Quantitative results revealed a significant reduction in anger scores among the treatment group (pretest M = 36.67, posttest M = 15.22, p < 0.001), indicating a strong effect of the intervention. The data met assumptions of normality (Shapiro-Wilk p > 0.05) and homogeneity of variance (Levene’s p = 0.249), supporting the validity of statistical analyses. Complementary qualitative data collected through participant observation and brief interviews emphasized improvements in emotional self-regulation, interpersonal communication, and peer support. These findings suggest that integrating self-control techniques into group counseling can serve as a practical and culturally responsive strategy for managing adolescent anger in Indonesian school contexts. The study contributes to the limited body of research on school-based mental health interventions in non-Western educational environments.